Estudo experimental de uma intervenção não farmacológica para promover equilíbrio emocional entre estudantes universitários - Bianchini, Camila (Universidade Federal de São Carlos, 2018)
Recent researches have revealed worrying rates of stress, anxiety and depression in college students. In the academic environment, negative emotional reactions and physical symptoms related to stress occur when curricular requirements exceed the student's ability, resources, or needs, leading to stress affecting negatively concentration, memory and problem solving, which can lead harm the student's performance. Therefore, it is important for college students learning how to manage stress while actively engaging with healthy challenges that promote growth. The purpose of this study was to evaluate the effects of an intervention to reduce stress, anxiety, and depression, and improve attention capacity ability in college students. An experimental study, not randomized, pre/posttest design with 59 undergraduate and strictu sensu postgraduate female students (treatment group (TG) = 27, control group (CG) = 32) in a Brazilian public university was performed between October and December 2016. TG completed an 8-week program, 2 and half hours per week with the Cultivating Emotional Balance course (CEB based course) and Hatha Yoga exercises. All participants completed the self-report questionnaires at baseline and after 8 weeks (Lipp Stress Symptons Inventory (ISSL), Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI) and the Mindful Attention Awareness Scale (MAAS) at baseline, and after 8 weeks). Descriptive analyzes, chi-square test, t-test, Wilcoxon-Mann-Whitney, Odds Ratio(OR) and Relative Risk(RR) tests were performed. All the applied questionnaries presented good reliability in the pre and post test. The post-test OR analysis indicated stress in the CG 2.77 higher than the GI; there was a reduction from 77.7% to 40.7% of GI participants who were in the stress resistance/exhaustion phase and a 42% reduction of stress complaint (RR = 0.58). Pre and post-test results for GI showed a significant reduction for BAI (p = 0.002) and BDI (p <0.001); there was no significant difference for MAAS (p = 0.078). Positive correlations of moderate intensity were identified between depression and anxiety (r = 0.761, p <0.01); the MAAS post test presented negative correlation with BAI (r = -0.615, p <0.01) and BDI (r = -0.597, p <0.01). The CEB based course associated with Hatha Yoga was able to reduce the stress, anxiety and symptoms of depression in university students, but it was not able to improve attention levels. The present intervention demonstraded as a possible tool for stress management among university students, presenting as advantages the possibility of being executed in group and the low cost for its implementation.
Experimental study of a non-pharmacological intervention to promote emotional balance in college students
Keywords: Estresse; Ansiedade; Depressão; Atenção; Estudantes universitários; Estudo de intervenção; Psychological stress; Anxiety; Depression; Attention; College students; Clinical trial; CIENCIAS DA SAUDE::ENFERMAGEM